Rheinische Braunkohle – Energieträger und vielseitiger Rohstoff im Wandel der Zeit. Issue 1 (20th November 2017) - Overhoff, Urs; Moser, Peter; Elsen, Reinhold; Vinzelberg, Gero; Eyll‐Vetter, Michael; Neuroth, Markus
Abstract: As Germany's most important, domestic fossil energy carrier, lignite plays a crucial role in electricity and heat production. Even though its share of the overall power production is decreasing due to a rising feed‐in from renewable energy sources, fossil energy carriers will go on providing base load and back‐up electricity in times when renewable energies are not able to produce enough electricity. Lignite and byproducts can also be used for material utilization. The production of hydrocarbons or extraction of important raw materials are examples.